2018
DOI: 10.1111/2047-3095.12233
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Surgical Wound Healing in Orthopedic Patients with Impaired Tissue Integrity According to Nursing Outcomes Classification

Abstract: PURPOSE To assess the surgical wound (SW) healing in orthopedic patients with Impaired tissue integrity according to the Nursing Outcomes Classification (NOC). METHODS A prospective longitudinal study performed with 24 patients. Data collection was performed through an instrument containing the NOC indicators. FINDINGS The indicators skin approximation, drainage, surrounding skin erythema, periwound edema, increased skin temperature, and foul wound odor presented a statistically significant increase when compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…The Wound healing: Primary intention and Infection Severity outcomes had a prevalence of 57% for nurses and 3% for physiotherapists. A study that evaluated the surgical wound of orthopedic patients showed that the Wound healing: Primary intention NO showed progressive improvement in the indicators of skin approximation, drainage, surrounding skin erythema, edema, increase skin temperature and foul wound odor when comparing the averages between the first and the last day of assessment (19) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Wound healing: Primary intention and Infection Severity outcomes had a prevalence of 57% for nurses and 3% for physiotherapists. A study that evaluated the surgical wound of orthopedic patients showed that the Wound healing: Primary intention NO showed progressive improvement in the indicators of skin approximation, drainage, surrounding skin erythema, edema, increase skin temperature and foul wound odor when comparing the averages between the first and the last day of assessment (19) .…”
Section: Discussionmentioning
confidence: 99%
“…Within the scope of the Nursing practice, the records prioritized the monitoring of the surgical wound due to the concern with the risk of infection for patients in the post-operative period of THA (19) . Intrinsically, when the healing status is monitored, the presence of signs and symptoms of infection is also assessed.…”
Section: Discussionmentioning
confidence: 99%
“…refusals, which resulted in a sample of 40 patients (20 in each group), based on previous studies (14)(15)(16)(17) .…”
Section: Population and Sample: Inclusion And Exclusion Criteriamentioning
confidence: 99%
“…These outcomes assess cell and tissue regeneration in wounds and the physiological functions of skin and mucous membranes, respectively (13) . NOC has been used in wound repair studies, in which it has demonstrated clinical applicability in different scenarios (14)(15)(16)(17) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation